1998
DOI: 10.1111/j.1439-0523.1998.tb01954.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in seed proteins from mutagen‐treated cultivars and selected lines of Vigna unguiculata L. Walp

Abstract: The storage protein profiles of the seeds of two IITA cowpea cultivars ('IT84E-124' and 'Vita 7') exposed to three mutagens -sodium azide (NaN3), ethyl methane sulphonate (EMS) and ^''Co gamma rays -and those of 18 selected M3 lines were investigated by sodium dodecyl sulphate (SDS)-polyacrylamide gel electrophoresis (PAGE). The total seed protein, globulin and albumin fractions showed differences in number and intensity of subunit bands, but the least differences were found in the albumin fraction. Both high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Tabatabei et al (2011) reported that human factors are very important for the association between accessions from different locations. Results within close range of similarity coefficient were similarly reported in many other species; for example, 0.82-0.24 in cowpea cultivars and 0.96-0.47 in sesame accessions (Osanyinpeju and Odeigah, 1998;Alege, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Tabatabei et al (2011) reported that human factors are very important for the association between accessions from different locations. Results within close range of similarity coefficient were similarly reported in many other species; for example, 0.82-0.24 in cowpea cultivars and 0.96-0.47 in sesame accessions (Osanyinpeju and Odeigah, 1998;Alege, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…The first mutant cultivar was produced in tobacco in Indonesia in 1936 and up to the recent time, 3220 cultivars in over 220 crop species have been developed and released to farmers all over the world [7]. However, little work has been reported on mutation breeding in cowpea [8]- [10], which has been widely used among other legume crops. An exception is India where 10 cowpea mutant cultivars have been released to farmers [11].…”
Section: Introductionmentioning
confidence: 99%
“…In cowpea, it has been reported that irradiation mutations have resulted in changes in morphological and reproductive traits [17], [18]. At the biochemical level, two cowpea cultivars have shown variation in number as well as intensity of protein bands after exposure to gamma rays [19], [20].…”
Section: Introductionmentioning
confidence: 99%